Implementasi Website Berita Online Menggunakan Metode Crawling Data dengan Bahasa Pemrograman Python - Sendi Algifari Rismawan (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
The implementation of online news websites is one of the requirements of the current digital era. This is because more and more people obtain information through the internet, and news spreads faster through online media. One way to obtain information from online news is by using the technique of data crawling. Data crawling is a computer program that automatically retrieves data from the web. This method enables efficient and structured data collection from various sources. In this research, the author will create an online news website using data crawling techniques with the Python programming language. The aim of this study is to create an online news website that can display news from various sources efficiently and systematically. This research will also provide an in-depth discussion of the concept of data crawling techniques and the use of programming languages such as Python and PHP (PHP: Hypertext Pre-processor) to implement online news websites, including the process of retrieving and storing data from various sources. The results of this study are expected to contribute to the development and inspiration for the development of online news websites using data crawling techniques. The research methodology used in this study is the Waterfall method, which is commonly used in software development. This method provides a structured approach to system development, which is used as a reference by the author in determining the research steps. This research also presents previous studies that have used data crawling methods, such as collecting culinary places in Bandar Lampung, collecting sparepart prices at PT Asuransi Sinar Mas, and identifying the needs of the West Nusa Tenggara community during the Covid-19 pandemic. These studies demonstrate the effectiveness of data crawling techniques for data collection and analysis purposes.